Case report: use of intra-aortic balloon pump (iabp) in high-risk percutaneous coronary intervention procedure - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2016)
Intra-aortic balloon pump (IABP) is often used in patients who undergo high risk percutaneous coronary intervention (PCI) procedures, particularly if associated with hemodynamic impairment. However, this device is still underused in this center. In this case report, a 65-year old male patient with triple vessel disease (chronic total occluded left anterior descending artery-LAD, and significant stenoses of left circumflex and right coronary arteries), low ejection fraction and preprocedure blood pressure, was reported to have IABP support applied before PCI. The intervention to penetrate the occluded LAD was not success. After procedure, the patient was observed in intensive care unit. Weaning of IABP was performed after about 30 hours usage, without complication.